2023
DOI: 10.33751/jhss.v7i1.7148
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Factors Behavioral Intention of The Generation Millennials in Using E-Wallets

Abstract: Technological advancements fueled by the internet revolution have transformed the financial services industry's image, resulting in modifications to electronic financial services. These service changes can be seen in almost all forms of financial services, such as banking, insurance, and stock trading, which are carried out using electronic media, such as E-wallets services. This study's primary goal is to discover how the Millennial generation uses digital wallet applications in terms of perceived ease of use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several previous studies found a significant influence of perceived usefulness on behavioral intention (Aris, 2015;Aris et al, 2016;Budi et al, 2021;Peng & Yan, 2022;Perwitasari, 2022;Widiar et al, 2023). However, several studies found an insignificant influence between perceived usefulness and behavioral intention (Muslichah, 2018;Nainggolan et al, 2023;Szajna, 1996).…”
Section: Technology Acceptance Modelmentioning
confidence: 93%
“…Several previous studies found a significant influence of perceived usefulness on behavioral intention (Aris, 2015;Aris et al, 2016;Budi et al, 2021;Peng & Yan, 2022;Perwitasari, 2022;Widiar et al, 2023). However, several studies found an insignificant influence between perceived usefulness and behavioral intention (Muslichah, 2018;Nainggolan et al, 2023;Szajna, 1996).…”
Section: Technology Acceptance Modelmentioning
confidence: 93%